2020
DOI: 10.3389/frma.2020.596624
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Biases in CORD-19 for Analyzing COVID-19 Literature

Abstract: On the behest of the Office of Science and Technology Policy in the White House, six institutions, including ours, have created an open research dataset called COVID-19 Research Dataset (CORD-19) to facilitate the development of question-answering systems that can assist researchers in finding relevant research on COVID-19. As of May 27, 2020, CORD-19 includes more than 100,000 open access publications from major publishers and PubMed as well as preprint articles deposited into medRxiv, bioRxiv, and arXiv. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
(70 reference statements)
1
8
0
Order By: Relevance
“…In a span of a few months, it appears that most gaps in the coverage of CORD-19 have been filled. This testifies to the efforts made by the CORD-19 team to expand the coverage of the dataset [ 21 ].…”
Section: The Cord-19 Datasetsupporting
confidence: 56%
“…In a span of a few months, it appears that most gaps in the coverage of CORD-19 have been filled. This testifies to the efforts made by the CORD-19 team to expand the coverage of the dataset [ 21 ].…”
Section: The Cord-19 Datasetsupporting
confidence: 56%
“…To retrieve the publications, Scopus ( http://www.scopus.com ) was accessed on March 12, 2021, and an advanced search was performed using a filter by country (Cuba), source (journals) and type of articles (article and review). Most of the terms used for the search were extracted from previous bibliometric articles [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] and the PubMed Medical Subject Headings (MeSH) related to the disease included in the MeSH catalog in its 2021 update were also used: COVID-19 vaccines, COVID-19 testing, COVID-19 serological testing and COVID-19 nucleic acid testing. The search strategy we used is shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Hence, in record time, an unprecedented avalanche of knowledge was generated and several publishers offered online and open access publications on the disease, which are now available to the scientific community. [4] This increase in scientific output was the subject of various bibliometric studies worldwide, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] in Latin America, [24][25][26][27][28] Iran, [29] India, [30] in nursing journals, [31] in relation to pediatrics [32] and a stroke, [33] as well as in comparison to other coronaviruses. [34,35] J o u r n a l P r e -p r o o f Cuban science has contributed significantly to the confrontation with COVID-19, facilitating the prediction, the improvement of therapeutic protocols and the improvement of action models for the reduction of risks and vulnerabilities in the face of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, predicting significant scientific achievements is a challenging enterprise as an increasing number of studies have revealed the unpredictable nature of scientific success [13]. On the other hand, recent advances in digital libraries and scientific publication indexing services such as Dimensions, Lens.org, and Microsoft Academic Graph (in addition to the Web of Science and Scopus) provide us with an unprecedented level of digital access to hundreds of millions of scientific publications and metadata [14,15]. These resources present new opportunities for developing the next-generation computational methods for explaining and predicting breakthroughs in science [16].…”
Section: Introductionmentioning
confidence: 99%